A Utilização do Jogo no Ensino de Porcentagem como auxiliar na Inter-Relação de Alunos Surdos e Não Surdos: uma proposta didática - CASTRO, Samara Andrade da Silva de (Universidade Federal do Tocantins, 2023)
The present research aimed to understand how the percentage teaching and learning process occurs with the use of games, enabling interaction between deaf and non-deaf students. Which was outlined by the following question: How can we use the game in teaching percentage, so that it can provide a better interaction between deaf and non-deaf students, in a way that facilitates the fixation of the content and helps in their learning? We used the technical precepts of the bibliographic review, gathering the history, laws, some details about the Brazilian Sign Language (LIBRAS) and the insertion/use of games for teaching mathematics with deaf and non-deaf students, in order to provide, among students, a guided interaction using the game providing new experiences and learning experiences. In this sense, we created the game entitled "Percentage of Inclusion", which consists of a board, in which students will have to develop activities that involve percentage, following some rules that can provide an egalitarian experience between the deaf and non-deaf. For which, we developed a didactic proposal, with methodological guidelines of requirements necessary to teach percentage, enjoying the game to obtain a better fixation, focusing on the interaction of deaf and non-deaf students. At the end of the studies, it was possible to infer that the use of games in the teaching of mathematics can arouse students' interest in the content being taught, however, one should work with caution when using them in teaching, following some criteria to maintain the focus on learning. We infer that it is possible to support the use of games to improve mathematics teaching, by providing other methods of communicating without using oral language or LIBRAS, which are, respectively, the mother tongue of non-deaf and deaf students.